Novel stiffeners exploiting internal pressurisation to enhance buckling behaviour under bending loads - Polenta, Valerio; Garvey, Seamus D.; Chronopoulos, Dimitrios; Long, Andy C.; Morvan, Herve (Elsevier, 2016)
The paper proposes a novel type of stiffener designed to bear bending loads by exploiting internal pressure effects. The stiffener is made of two adjacent thin-walled pipes (r/t≥50) jointed with a connecting strip. Such a structure is shown to have higher performance against buckling failure compared to a single pipe and its geometry allows for good exploitation of internal pressurisation.